Application of QFD in Service Quality Improvement: The Case of Pasar Malam Batubulan Services - Dewa Ayu Anom Yuarini; G.P. Ganda Putra; Luh Putu Wrasiati; Gede Wahyu Wardana; I Gede Arie Mahendra Putra; Luh Dian Rna Fajarini (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
Dewi Sri Market, located at Batubulan Terminal, Sukawati District, Gianyar, Bali, is one of the island’s tourist destinations, offering a unique shopping experience with diverse culinary choices, performances, clothing, and entertainment for children, commonly known as Pasar Malam Batubulan. This study aims to identify the attributes considered important by the public regarding Pasar Malam Batubulan, measure the levels of importance and satisfaction related to service quality, and formulate strategies to improve service quality. The analysis employs Quality Function Deployment (QFD), with variables derived from the five service quality dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Based on the QFD analysis, the attribute with the highest importance value was the tangibles dimension, specifically toilet facilities (4.83), followed by vendor politeness (4.82), cleanliness and comfort of the market area (4.80), vendor friendliness (4.80), parking availability (4.79), and lighting quality (4.78). Other attributes that were rated highly included vendor product knowledge (4.68), service responsiveness (4.66), price-to-portion fairness (4.66), and market layout (4.64). However, satisfaction scores revealed a considerable gap, with salesperson friendliness receiving the highest score (4.05) and toilet facilities scoring the lowest (3.42), highlighting critical gaps in service quality. Based on respondent characteristics, the recommended strategies include introducing digital payment systems such as QRIS or digital wallets. Sustained capacity building for merchants, along with regular evaluations, is considered essential to measure the long-term impact of these initiatives and to assess their readiness for digital transformation. These findings underscore that enhancing basic facilities and adopting digital payment systems are strategic measures to improve customer satisfaction and align traditional markets with the evolving demands of the digital era.